Organochlorinated pesticide contaminants in Golfo Dulce, Costa Rica - Spongberg, Alison L.; Davis, Penny (Revista de Biología Tropical, 1998)
The organic contaminant load within the sediments of Golfo Dulce has so far gone unstudied. Concentrations of persistent pesticides were ascertained for comparison with future contaminant loads and for evaluation of response of biota to these compounds. Forty seven sediment cores were collected from the shores of Golfo Dulce. Costa Rica for quantification of persistent pesticide contamination, particle size distribution, and organic matter content The gulf has to date had only minimal accumulations of pesticides. The deep anoxic fine-grained organic sediments in the northern portion of the gulf have had minimal impact from humans. However, evidence of pesticide metabolites. and aromatic hydrocarbons may indicate an accumulation of some contaminants and degradation of others in this zone. The Esquinas River sediments were found to contain numerous persistent pesticides. such as a, B, y, and 6-BHC. The Coto-Colonado River sediments are coarser in texture. with low organic contents and may not retain pesticides efficiently. The pesticide load from this river may be transported great distances within the gulf. The Golfito area had link pesticide contamination, however, aromatic and diesel hydrocarbons were in great abundance in the sediments.